Urgency of Government Protection on Consumers in the Concept of The Rule of Law - et al., Aditya Bagus Kuncoro (International Journal of Advanced Science and Technology, 2019)
This study aims to find out about the extent of the government’s important role in legal protection for consumers in Indonesia, based on the concept of the rule of law. The government has established a Consumer Dispute Settlement Agency (BPSK) whose initial goal is to provide legal protection for consumers who are often ignored by the law itself, but in its development BPSK has not run as it should because the fact is that BPSK currently lacks independence because of its position in the ministry trade and industry, from this fact the researchers tried to apply it through the concept of the rule of law. The research method is carried out with a doctrinal and non-doctrinal approach, because the law is not only in concepts as a whole of principles and rules, but also includes institutions and processes that realize the enactment of rules in society. The results of the study are that the concept of consumer protection in the concept of legal state is how to realize the rights and obligations carried out between legal relations of consumers and suppliers of balanced goods or services and must realize the concept of equality before the law and uphold human rights as the main requirement. Achieving the concept of equality before law and recognition of human rights in consumer protection will automatically increase public compliance with the law and the government itself and create good governance.